Analysis of The Electronic Fuel Injector Operation - Sebok, Milan; Gutten, Miroslav; Adamec, Juraj; Glowacz, Adam; Roj, Jerzy (Communications - Scientific letters of the University of Zilina, 2018)
The paper deals with research results of electronic fuel system injection (FSI) and its possible measurement for diagnostic analysis. In the parts of the paper the design and operation of a typical fuel injection system is described and its electronic part is analysed. The procedure for the detection of the injector malfunction based on the analysis of differential current characteristic has also been proposed. In the end the differences in the electrical parameters of the individual fuel injectors on the based comparison of reference and failure current are shown.